(untitled) (Global Scientific Review, 2023)
The article analyzes the physical and chemical foundations of the in-situ leaching process, data processing using approximate analytical solutions to predict the required parameters and verify the reliability of the developed process control model, and conduct a system analysis of the in-situ leaching process as an object of study